Memorial reflexivo: contribuições do magistério na minha formação acadêmica do PARFOR - MORAES, Maria das Dores Pinheiro (2023)
In this reflective memorial is exposed the history and the analysis of the process of formation, that for me was experienced, in the construction and exercise of the teaching profession. For such an approach it became necessary to describe facts and events that were directly or indirectly related to my teaching. Thus, I describe the processes of formation, from my childhood to the conclusion of the course of full licentiate in Pedagogy by the Freire platform in Ufpa, within the chronological context to highlight the relevance of education in my life. Also discussed are the interpersonal relationships built in the day to day life with students and co-workers. In order to carry out this work, each event was based on a theoretical basis based on authors such as: Saviani (1994), Libâneo (1994), Aries (1981), Santos (2006), Zabala (1998), among others. In this sense, the reconstruction of my history contributed to the reflection of my teaching practice before and after the higher education in the course of Pedagogy, which among other things considers education an unfinished process and therefore free of static and amorphous thoughts. Thanks to the training obtained in the course of Pedagogy my ideas have been reconfigured for a continuous improvement.